2013
DOI: 10.1073/pnas.1222845110
|View full text |Cite
|
Sign up to set email alerts
|

Defining a protective epitope on factor H binding protein, a key meningococcal virulence factor and vaccine antigen

Abstract: Mapping of epitopes recognized by functional monoclonal antibodies (mAbs) is essential for understanding the nature of immune responses and designing improved vaccines, therapeutics, and diagnostics. In recent years, identification of B-cell epitopes targeted by neutralizing antibodies has facilitated the design of peptide-based vaccines against highly variable pathogens like HIV, respiratory syncytial virus, and Helicobacter pylori; however, none of these products has yet progressed into clinical stages. Line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
166
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(181 citation statements)
references
References 38 publications
10
166
0
1
Order By: Relevance
“…meningitides for complement evasion (e.g. Poltermann et al , 2007; Malito et al , 2013; reviewed in Zipfel et al , 2007). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…meningitides for complement evasion (e.g. Poltermann et al , 2007; Malito et al , 2013; reviewed in Zipfel et al , 2007). …”
Section: Discussionmentioning
confidence: 99%
“…The use of microbial FH‐receptors as vaccine candidates is currently been studied for meningococcal infections (Malito et al , 2013; Rippa et al , 2015), and crucial for such approach the vaccine candidate has to be mutated such that the protein loses its FH‐binding function in order not to interfere with the human complement system.…”
Section: Discussionmentioning
confidence: 99%
“…In this way, the deuterium uptake kinetics directly reflects the backbone dynamics of the protein structure. For a protein-protein complex, the binding interface will usually exhibit a decreased deuterium uptake due to having reduced backbone dynamics and being shielded from the solvent (22).…”
Section: Significancementioning
confidence: 99%
“…By increasing the half-life of the alternative pathway C3 convertase, properdin antagonizes the functional activity of complement factor H, an abundantly expressed plasma component, which promotes inactivation of the alternative pathway C3 convertase and of all C5 convertases of complement by accelerating the decay of these enzyme complexes through binding to complex-bound C3b and by serving as a cofactor in the factor I-mediated conversion of C3b to its inactive form, termed iC3b (35). Interestingly, the two pathogens used in this study were previously shown to express distinct microbial surface components that sequester factor H from host plasma, leading to resistance to the complement-mediated immune clearance of these pathogens (36,37).…”
mentioning
confidence: 92%